Precarious passages : the diasporic imagination in contemporary Black Anglophone fiction - Valkeakari, Tuire (University Press of Florida, 2017)
Drawing from Caribbean, U.S., Canadian, and British novels, Tuire Valkeakari examines how fiction written in English contributes to and comments upon the continuing transnational constructions of black diasporic identity. Valkeakari argues for the critical role that secular culture in general and fiction in particular play in creating symbolic connections to sustain the idea of a black diasporic community.